2020
DOI: 10.1158/1078-0432.ccr-19-3845
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Ex Vivo TIL Expansion Is Highly Influenced by Spatial Heterogeneity of the Tumor T-Cell Repertoire and Differences in Intrinsic In Vitro Growth Capacity between T-Cell Clones

Abstract: The outcome of ex vivo TIL expansion is highly influenced by spatial heterogeneity of the tumor Tcell repertoire and differences in intrinsic in vitro growth capacity between T-cell clones AUTHORS -

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 49 publications
0
43
1
Order By: Relevance
“…As these cancer-specific T cells become less responsive to interleukin-2 (IL-2), which mediates T-cell expansion, they might become diluted by bystander T cells during the process of expansion in TIL-ACT, with an overall loss of TCR repertoire. 15,191,192 However, despite their functional impairment, it is widely appreciated that exhausted T cells are often tumour-specific and can still retain some control over tumour growth, as shown by the great clinical effect of blocking programmed death protein 1 (PD-1) or programmed cell death ligand 1 (PD-L1) axis in solid tumours. 193,194 Exhausted T cells express increased levels of inhibitory immune checkpoint molecules, such as PD-1, CTLA-4, LAG3 and TIM3, 195 and decreased levels of the adhesion/ costimulatory molecule CD2, both of which might attenuate anti-tumour T-cell responses in tumours.…”
Section: Ex Vivo Drug Modulation Modifications Of Culturing Conditionmentioning
confidence: 99%
“…As these cancer-specific T cells become less responsive to interleukin-2 (IL-2), which mediates T-cell expansion, they might become diluted by bystander T cells during the process of expansion in TIL-ACT, with an overall loss of TCR repertoire. 15,191,192 However, despite their functional impairment, it is widely appreciated that exhausted T cells are often tumour-specific and can still retain some control over tumour growth, as shown by the great clinical effect of blocking programmed death protein 1 (PD-1) or programmed cell death ligand 1 (PD-L1) axis in solid tumours. 193,194 Exhausted T cells express increased levels of inhibitory immune checkpoint molecules, such as PD-1, CTLA-4, LAG3 and TIM3, 195 and decreased levels of the adhesion/ costimulatory molecule CD2, both of which might attenuate anti-tumour T-cell responses in tumours.…”
Section: Ex Vivo Drug Modulation Modifications Of Culturing Conditionmentioning
confidence: 99%
“…Of note, comparison of the use of allogeneic versus autologous feeder cells during the TIL expansion phase revealed that both have a similar risk of emergence of new TCR clonotypes. 31 Cells were passaged when multiple clusters of dividing T cells were observed, which was usually once or twice during the two-week REP culture period. The expanded T cells were cryopreserved in freezing medium.…”
Section: Til Culturementioning
confidence: 99%
“…In a recent study, Schober and colleagues studied TCR repertoire evolution in the context of latent CMV infection and found that, although high-affinity TCRs dominated T cell responses at early times after infection, low affinity TCRs emerged over time, owing to cellular differentiation and senescence (and not exhaustion) of high affinity ones (124). In a recent publication, Poschke and coauthors exploited TCR deep sequencing to characterize TILs before and after in vitro culture and found that dominant T cell clones were lost during TIL culture because of poor expansion potential, in favor of less represented ones (125). The authors argue that spatial heterogeneity of the tumor T cell repertoire, as well as differences in intrinsic in vitro growth capacity between individual T cell clones, influenced the T cell preparation.…”
Section: Tcr Affinity/aviditymentioning
confidence: 99%